Abdominal obesity, weight gain during adulthood and risk of liver and biliary tract cancer in a European cohort. Issue 3 (13th June 2012) - Schlesinger, Sabrina; Aleksandrova, Krasimira; Pischon, Tobias; Fedirko, Veronika; Jenab, Mazda; Trepo, Elisabeth; Boffetta, Paolo; Dahm, Christina C.; Overvad, Kim; Tjønneland, Anne; Halkjær, Jytte; Fagherazzi, Guy; et al.
Abstract General obesity has been positively associated with risk of liver and probably with biliary tract cancer, but little is known about abdominal obesity or weight gain during adulthood. We used multivariable Cox proportional hazard models to investigate associations between weight, body mass index, waist and hip circumference, waist‐to‐hip and waist‐to‐height ratio (WHtR), weight change during adulthood and risk of hepatocellular carcinoma (HCC), intrahepatic (IBDC) and extrahepatic bile duct system cancer [EBDSC including gallbladder cancer (GBC)] among 359, 525 men and women in the European Prospective Investigation into Cancer and Nutrition study. Hepatitis B and C virus status was measured in a nested case–control subset. During a mean follow‐up of 8.6 years, 177 cases of HCC, 58 cases of IBDC and 210 cases of EBDSC, including 76 cases of GBC, occurred. All anthropometric measures were positively associated with risk of HCC and GBC. WHtR showed the strongest association with HCC [relative risk (RR) comparing extreme tertiles 3.51, 95% confidence interval (95% CI): 2.09–5.87; ptrend < 0.0001] and with GBC (RR: 1.56, 95% CI: 1.12–2.16 for an increment of one unit in WHtR). Weight gain during adulthood was also positively associated with HCC when comparing extreme tertiles (RR: 2.48, 95% CI: 1.49–4.13; <0.001). No statistically significant association was observed between obesity and risk of IBDC and EBDSC. Our results provide evidence of an association between obesity, particularly abdominal obesity, and risk of HCC and GBC. Our findings support public health recommendations to reduce the prevalence of obesity and weight gain in adulthood for HCC and GBC prevention in Western populations.